2018
DOI: 10.1111/tpj.13921
|View full text |Cite
|
Sign up to set email alerts
|

A chromatin loop represses WUSCHEL expression in Arabidopsis

Abstract: WUSCHEL (WUS) is critical for plant meristem maintenance and determinacy in Arabidopsis, and the regulation of its spatiotemporal expression patterns is complex. We previously found that AGAMOUS (AG), a key MADS-domain transcription factor in floral organ identity and floral meristem determinacy, can directly suppress WUS expression through the recruitment of the Polycomb group (PcG) protein TERMINAL FLOWER 2 (TFL2, also known as LIKE HETEROCHROMATIN PROTEIN 1, LHP1) at the WUS locus; however, the mechanism by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 64 publications
1
38
0
1
Order By: Relevance
“…AGAMOUS (AG), a MADS box transcription factor (Yanofsky et al, 1990), is a key regulator in this process and triggers flower meristem termination by repressing WUS expression (Lohmann et al, 2001; Lenhard et al, 2001). This repression by AG can be direct, by recruiting polycomb group (PcG) factors and promoting a chromatin loop that blocks the recruitment of RNA polymerase II at the WUS locus (Liu et al, 2011; Guo et al, 2018), but also indirect through activation of KNUCKLES (KNU; a C2H2 Zn-finger transcription factor) (Sun et al, 2009). KNU is recruited to the WUS locus by MINI ZINC FINGER2 to form a complex together with HISTONE DEACETYLASE-like HDA19 and TOPLESS, which in turn inhibits WUS expression (Sun et al, 2009, 2014; Bollier et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…AGAMOUS (AG), a MADS box transcription factor (Yanofsky et al, 1990), is a key regulator in this process and triggers flower meristem termination by repressing WUS expression (Lohmann et al, 2001; Lenhard et al, 2001). This repression by AG can be direct, by recruiting polycomb group (PcG) factors and promoting a chromatin loop that blocks the recruitment of RNA polymerase II at the WUS locus (Liu et al, 2011; Guo et al, 2018), but also indirect through activation of KNUCKLES (KNU; a C2H2 Zn-finger transcription factor) (Sun et al, 2009). KNU is recruited to the WUS locus by MINI ZINC FINGER2 to form a complex together with HISTONE DEACETYLASE-like HDA19 and TOPLESS, which in turn inhibits WUS expression (Sun et al, 2009, 2014; Bollier et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…At stage 3 of floral development (Smyth et al, 1990), AG expression is induced by WUS and LFY at the center of the FM, and WUS expression is turned off at stage 6, resulting in FM determinacy (Lohmann et al, 2001). AG indirectly represses WUS expression through KNUCKLES (Sun et al, 2009(Sun et al, , 2019, and AG also directly represses WUS through the TERMINAL FLOWER2 (TFL2)-AG complex that triggers chromatin loop formation at the WUS locus (Liu et al, 2011;Guo et al, 2018). As a central hub in this network, AG is regulated by numerous factors at the transcriptional, posttranscriptional and protein level through genetic and epigenetic mechanisms (Cao et al, 2015;Xu et al, 2019).…”
Section: Genetic Regulation Of Sam Maintenance and Fm Determinacymentioning
confidence: 99%
“…Researchers have shown that two tandem CArG boxes in the WUSCHEL ( WUS ) 3′ cis ‐regulatory element (CRE) region are important for WUS expression regulation, but the mechanism whereby WUS is repressed remains unclear . We designed a pair of sgRNAs across the two CArG boxes to delete the fragment.…”
Section: Crispr/cas9‐created Mutations In Plantsmentioning
confidence: 99%
“…We designed a pair of sgRNAs across the two CArG boxes to delete the fragment. A mutant with an approximately 80‐bp deletion across the CArG boxes was obtained, offering direct evidence that the CArG boxes in the WUS 3′ CRE region are critical for chromatin loop formation . Thus, CRISPR/Cas9 can be used to create specific mutants to analyze the DNA element(s) required for transcription factor binding.…”
Section: Crispr/cas9‐created Mutations In Plantsmentioning
confidence: 99%